The Effect of Capital Structure and Profitability on Firm Value of Listed Companies Under Indonesia Stock Exchange’s Non-cyclical Consumer Sector - Olivia Georgina Gultom; Herman Karamoy; Sintje Rondonuwu (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of capital structure and profitability on firm value in the consumer non-cyclical sector listed on the Indonesia Stock Exchange for 2016 – 2020 periods. Capital structure is measured by Debt to Equity Ratio (DER), profitability is measured by Return on Equity (ROE), and firm value is measured by Price to Book Value (PBV). This study uses quantitative method with purposive sampling as method of selecting samples. 34 samples of companies were obtained from 98 companies. The data analysis is multiple linear regressions with IBM SPSS 26 as data processing. The results of this study indicate that partially capital structure had a negative effect on firm value, which means the rises on capital structure will reduce the firm value and profitability had a positive effect on firm value, which means increased profitability will increased firm value. Simultaneously capital structure and profitability have a significant effect on firm value.